2013
DOI: 10.1530/eje-12-0814
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory receptor 51E1 protein as a potential novel tissue biomarker for small intestine neuroendocrine carcinomas

Abstract: Objective: Late diagnosis hinders proper management of small intestine neuroendocrine carcinoma (SI-NEC) patients. The olfactory receptor, family 51, subfamily E, member 1 (OR51E1) has been reported as a potential novel SI-NEC marker, without protein expression recognition. Thus, we further studied whether the encoded protein may be a novel SI-NEC clinical biomarker. Design: OR51E1 coding sequence was cloned using total RNA from SI-NEC patient specimens. Quantitative real-time PCR analysis explored OR51E1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 24 publications
0
55
0
Order By: Relevance
“…A previous study showed that an olfactory receptor, OR51E2, is expressed in prostate cancer cells and that activation of OR51E2 by its ligand, b-ionone and inhibited proliferation of prostate cancer cells (29). Another olfactory receptor family member, OR51E1, was reported to be a potential novel biomarker for small intestine neuroendocrine carcinoma (30). Expression of the olfactory receptor OR13C4 was shown to be significantly associated with risk of pancreatic cancer by pathway analysis in a genome-wide association study (31).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that an olfactory receptor, OR51E2, is expressed in prostate cancer cells and that activation of OR51E2 by its ligand, b-ionone and inhibited proliferation of prostate cancer cells (29). Another olfactory receptor family member, OR51E1, was reported to be a potential novel biomarker for small intestine neuroendocrine carcinoma (30). Expression of the olfactory receptor OR13C4 was shown to be significantly associated with risk of pancreatic cancer by pathway analysis in a genome-wide association study (31).…”
Section: Discussionmentioning
confidence: 99%
“…Their discovery sparked a controversial discussion about the potential function of such “ectopically expressed” ORs. Many groups have reported mammalian OR expression at the transcript and/or protein level in various healthy as well as pathophysiologically altered tissues such as prostate cancer [19, 25, 31, 34, 70, 101, 105, 109, 111, 115]. …”
Section: Introductionmentioning
confidence: 99%
“…OR51E1 mRNA expression has been detected in normal brain (Vanti et al 2003) and prostate tissue (Weigle et al 2004). Furthermore, cancer cells, such as prostate carcinoma cells (Weigle et al 2004, Fuessel et al 2006 and small intestine neuroendocrine carcinoma (SI-NEC) cells (Leja et al 2009, Cui et al 2013, have been shown to express high levels of OR51E1. The pathophysiological role of OR51E1 in tumorigenesis and tumor progression has not been elucidated.…”
mentioning
confidence: 99%